Labors of Love : Nursing Homes and the Structures of Care Work - Rodriquez, Jason, 1978- (Book collections on Project MUSE., 2014)
Every day for the next twenty years, more than 10,000 people in the United States will turn 65. With life expectancies increasing as well, many of these Americans will eventually require round-the-clock attention-and we have only begun to prepare for the challenge of caring for them. In Labors of Love, Jason Rodriquez examines the world of the fast-growing elder care industry, providing a nuanced and balanced portrait of the day-to-day lives of the people and organizations that devote their time to supporting America's aging population. Through extensive ethnographic research, interviews with.